Physiological and Parasitological Interactions: Investigating Host Responses to Parasitic Infections through Experimental Analysis: Integrasi Kecerdasan Buatan untuk Pemantauan dan Evaluasi Strategi Pengendalian Hayati di Lapangan - Aliaa Kadhem Mohsin (Academia Open, 2026)
General Background Parasitic infections remain a major challenge in human and veterinary health due to their systemic physiological and immunological consequences. Specific Background Beyond tissue damage, parasites induce metabolic disturbances and immune modulation that influence disease progression. Knowledge Gap Integrated experimental evidence linking physiological alterations with immune cell activation and cytokine regulation remains limited. Aims This study aimed to investigate host physiological responses and immune dynamics during experimental Toxoplasma gondii and Plasmodium berghei infections. Results Infected hosts exhibited significant weight loss, fever, hypoglycemia, elevated CD4+ and CD8+ T cell activation, increased pro-inflammatory cytokines IL-6, TNF-α, IFN-γ, and concurrent upregulation of IL-10. Gene expression analysis confirmed significant modulation of IL-6 and IL-10. Novelty The study provides an integrated assessment of physiological parameters, immune activation, cytokine production, and gene expression within a single experimental framework. Implications These findings highlight the complex balance between immune activation and regulation during parasitic infections and support the need for therapeutic strategies targeting immune modulation to improve parasite control while limiting immunopathology. Keywords: Parasitic Infection, Host Physiology, Immune Response, Cytokine Regulation, Experimental Model Key Findings Highlights: Experimental infection induced marked metabolic and thermoregulatory alterations in hosts. Adaptive immune activation involved significant CD4+ and CD8+ T cell responses. Concurrent pro- and anti-inflammatory signaling reflected immune regulation during infection.